2021
DOI: 10.3389/fnins.2021.698777
|View full text |Cite
|
Sign up to set email alerts
|

Desire for Success Awakens: Proof of Competence Restoration in a Non-competitive Environment

Abstract: Pioneering studies reported that individuals who worked on a highly difficult task and experienced competence frustration beforehand would activate a restorative process and show enhanced autonomous motivation in a subsequent irrelevant activity. In this follow-up study, we explored the effect of prior competition outcome on one’s autonomous motivation in a subsequent non-competitive environment. According to our experimental manipulation, participants were randomly assigned to two treatment groups (a winning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…This result is in line with previous studies which reported that individuals perceive the consistent choice with others as a recognition and reward ( Klucharev et al, 2009 ; Nook and Zaki, 2015 ; Wang et al, 2019 ). Previous studies indicated that the FRN may originate from the anterior cingulate cortex ( Kiehl et al, 2000 ; Holroyd et al, 2004 ; San Martín, 2012 ), and distinguishes between positive and negative feedback ( Holroyd and Coles, 2002 ; Cohen et al, 2007 ; Meng et al, 2021 ). Besides the valence of the feedback, positive and negative feedback can be defined in terms of the discrepancy between the feedback and one’s expectation.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with previous studies which reported that individuals perceive the consistent choice with others as a recognition and reward ( Klucharev et al, 2009 ; Nook and Zaki, 2015 ; Wang et al, 2019 ). Previous studies indicated that the FRN may originate from the anterior cingulate cortex ( Kiehl et al, 2000 ; Holroyd et al, 2004 ; San Martín, 2012 ), and distinguishes between positive and negative feedback ( Holroyd and Coles, 2002 ; Cohen et al, 2007 ; Meng et al, 2021 ). Besides the valence of the feedback, positive and negative feedback can be defined in terms of the discrepancy between the feedback and one’s expectation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the finding that FRN was not affected by the levels of goal score suggests, at least, that the settings of the levels of goal scores did not affect participants' boredom and positive emotions during the current task. However, previous studies have reported FRN's role as indicating intrinsic motivation (Ma et al, 2014a;Fang et al, 2018;Meng et al, 2021) and have yielded inconsistent…”
mentioning
confidence: 93%
“…Consistent with reinforcement learning, FRN reflects extraction of motivationally significant outcomes (Pfabigan et al, 2010 ). Recent research has demonstrated that FRN amplitudes calculated from the difference wave between the ERP to incorrect feedback and one to correct feedback are related to intrinsic motivation (Ma et al, 2014a ; Fang et al, 2018 ; Meng et al, 2021 ). The FRN response is also modulated by affective mood states, such as positive emotion (Zhao et al, 2016 ; Paul and Pourtois, 2017 ) or boredom (Milyavskaya et al, 2019 ), which are presumably induced by the degree of intrinsic motivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People's well-being in the workplace is a major concern of contemporary organizations, as there emerges a large number of "walking dead" who are skilled at work, but tired at heart. To the managers of contemporary organizations, maintaining their employees' affective well-being and motivating them in a proper manner requires lots of managerial wisdom (Meng et al, 2021). A burgeoning line of literatures suggests that meaningfulness is a fundamental human need (Yeoman, 2014), as individuals are found to actively pursue meaning in their lives, especially in the work setting.…”
mentioning
confidence: 99%